Performance comparison of three trypsin columns used in liquid chromatography - Šlechtová, Tereza; Gilar, Martin; Kalíková, Květa; Moore, Stephanie M; Jorgenson, James W; Tesařová, Eva (Journal of chromatography. A, 2017)
Trypsin is the most widely used enzyme in proteomic research due to its high specificity. Although the in-solution digestion is predominantly used, it has several drawbacks, such as long digestion times, autolysis, and intolerance to high temperatures or organic solvents. To overcome these shortcomings trypsin was covalently immobilized on solid support and tested for its proteolytic activity. Trypsin was immobilized on bridge-ethyl hybrid silica sorbent with 300Å pores, packed in 2.1×30mm column and compared with Perfinity and Poroszyme trypsin columns. Catalytic efficiency of enzymatic reactors was tested using Nα-Benzoyl-l-arginine 4-nitroanilide hydrochloride as a substrate. The impact of buffer pH, mobile phase flow rate, and temperature on enzymatic activity was investigated. Digestion speed generally increased with the temperature from 20 to 37°C. Digestion speed also increased with pH from 7.0 to 9.0; the activity of prototype enzyme reactor was highest at pH 9.0, when it activity exceeded both commercial reactors. Preliminary data for fast protein digestion are presented.
Keywords: Trypsin; enzymy imobilizované; Chromatography, Liquid; Digestion efficiency; trypsin; chromatografie kapalinová; Activity; Enzymes, Immobilized; Immobilized enzymatic reactor